Determinants of acceptance of cervical cancer screening in Dar es Salaam, Tanzania - Kahesa Crispin; Kjaer Susanne; Mwaiselage Julius; Ngoma Twalib; Tersbol Britt; Dartell Myassa; Rasch Vibeke (BMC, 2012)
Abstract Objective To describe how demographic characteristics and knowledge of cervical cancer influence screening acceptance among women living in Dar es Salaam, Tanzania. Methods Multistage cluster sampling was carried out in 45 randomly selected streets in Dar es Salaam. Women between the ages of 25-59 who lived in the sampled streets were invited to a cervical cancer screening; 804 women accepted and 313 rejected the invitation. Information on demographic characteristics and knowledge of cervical cancer were obtained through structured questionnaire interviews. Results Women aged 35-44 and women aged 45-59 had increased ORs of 3.52 and 7.09, respectively, for accepting screening. Increased accepting rates were also found among single women (OR 2.43) and among women who had attended primary or secondary school (ORs of 1.81 and 1.94). Women who had 0-2 children were also more prone to accept screening in comparison with women who had five or more children (OR 3.21). Finally, knowledge of cervical cancer and awareness of the existing screening program were also associated with increased acceptance rates (ORs of 5.90 and 4.20). Conclusion There are identifiable subgroups where cervical cancer screening can be increased in Dar es Salaam. Special attention should be paid to women of low education and women of high parity. In addition, knowledge and awareness raising campaigns that goes hand in hand with culturally acceptable screening services will likely lead to an increased uptake of cervical cancer screening.